Antispasmodic and bronchorelaxant activities of Salsola imbricata are mediated through dual Ca+2 antagonistic and β-adrenergic agonistic effects - Naveed Aslam; Khalid Hussain Janbaz (Taylor & Francis Group, 2017)
Context: Salsola imbricata Forssk. (Chenopodiaceae) has folkloric repute for the treatment of various gastrointestinal and respiratory ailments. Objective: The present study investigates spasmolytic and bronchorelaxant effects of S. imbricata. Materials and methods: The crude aqueous-ethanol extract of the aerial parts of S. imbricata and its fractions, in cumulative concentrations (0.01-10 mg/mL), were tested on contractions of isolated rabbit jejunum and tracheal preparations. Furthermore, concentration response curves (CRCs) of Ca+2 and carbachol were constructed in the absence and presence of the extract. Standard organ bath methods were used. Results: The crude extract relaxed spontaneous, K+ (80 mM) and carbachol (1 μM)-induced contractions in jejunum preparations with respective EC50 values of 0.40 (0.35-0.46), 0.69 (0.60-0.79) and 0.66 (0.57-0.75) mg/mL. It shifted Ca+2 CRCs rightward in nonparallel manner. In isolated tracheal preparations, the crude extract caused relaxation of K+ (80 mM) and carbachol (1 μM)-induced contractions with EC50 values of 0.86 (0.75-0.98) and 0.74 (0.66-0.84) mg/mL, respectively. It displaced carbachol CRCs rightward with suppression of maximal response. In both tissues, pretreatment with propranolol (1 μM) caused rightward shift in inhibitory CRCs of the extract against carbachol-induced contractions. The ethyl acetate fraction was found more potent in relaxing smooth muscle contractions than the parent extract and its aqueous fraction. Discussion and conclusion: The results suggest that the spasmolytic and bronchorelaxant activities of S. imbricata are related to Ca+2 antagonistic and β-adrenergic agonistic effects, thus justifying some of the traditional uses of the plant.